(untitled) (Baghdad Science Journal, 2018)
One of the concerns of adopting an e-voting systems in the pooling place of any critical elections is the possibility of compromising the voting machine by a malicious piece of code, which could change the votes cast systematically. To address this issue, different techniques have been proposed such as the use of vote verification techniques and the anonymous ballot techniques, e.g., Code Voting. Verifiability may help to detect such attack, while the Code Voting assists to reduce the possibility of attack occurrence. In this paper, a new code voting technique is proposed, implemented and tested, with the aid of an open source voting. The anonymous ballot improved accordingly the paper audit trail used in this machine. The developed system, which we called CVOTING, further demonstrated the efficacy of the Code Voting technique against systematic vote change attacks and provides some features to make it easily configurable for different elections and elections in countries with right-to-left and up-to-down languages.